Investigation of structure of CaO-Al2O3-SiO2 melts as a basis for the development of new agglomerated welding fluxes and industrial refractories - Vladimir, Sokol'skii; Pruttskov, Dmitriy; Busko, Victor; Kazimirov, Volodimir; Roik, Oleksandr; Chyrkin, Anton; Galinich, Volodimir; Goncharov, Igor (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
A significant number of welding fluxes and industrial ceramics are produced in the Ukraine. The production of these materials is sufficient for both domestic needs and significant export. It is assumed that the ternary CaO-Al2O3-SiO2 system may become the basis for the development of agglomerated welding fluxes and technical ceramics. Three samples of ternary CaO-Al2O3-SiO2 system were studied by means of high-temperature XRD above the melting point: 23.3CaO-14.7Al2O3-62.0SiO2 wt. % (sample 1, eutectic), 9.8CaO-19.8Al2O3-70.4SiO2 wt. % (sample 2, eutectic), 15.6CaO-36.5Al2O3-47.9SiO2 wt. % (sample 3). Experimental scattering intensity curves, structure factors and the radial distribution function of atoms were obtained. The structural parameters of short-range order were calculated using melt structure models obtained by Reverse Monte Carlo method. The existence of nanocrystalline associates of the mullite or sillimanite type immersed in the slag matrix is assumed. The calcium ions are presumed to coordinate around these associates being in turn surrounded by oxygen anions of the melt. Such a structure might be regarded as a colloidal solution. The mullite nanoparticle comprises the core of the nanoaggregate matched by the calcium ions while the other melt atoms form the outer sphere of the nanoparticle